A high-quality round-shaped monolayer MoS2 domain and its transformation. Issue 1 (8th December 2015) - Xie, Shuang; Xu, Mingsheng; Liang, Tao; Huang, Guowei; Wang, Shengping; Xue, Guobiao; Meng, Nan; Xu, Yang; Chen, Hongzheng; Ma, Xiangyang; Yang, Deren
Abstract : Transformation from triangle to truncated triangle and round MoS2 domains is realized by controlling the thermodynamic or kinetic growth regime. Abstract : MoS2 is widely used in many fields including spin-valleytronics, logic transistors, light emitting devices, clean energy and biology. However, controllable synthesis of two-dimensional MoS2 sheets remains a great challenge. We report the formation of round-shaped monolayer MoS2 domains with a tunable size and the shape transformation from triangle to round. A qualitative interpretation of the formation mechanism is presented and the process can be controlled by either a thermodynamic or a kinetic growth regime depending on the growth rate. The round-shaped MoS2 domains show a high electron mobility of 1.39 cm 2 V −1 s −1, comparable to the mechanically exfoliated counterparts. Our study reveals the dominant factors that influence the synthesis of MoS2 and improves our understanding of the nucleation and growth mechanisms of MoS2, towards fine control over the synthesis of MoS2 and other TMDs.